Embattled nation : Canada's wartime election of 1917 - Dutil, Patrice A., 1960-; MacKenzie, David, 1953- (Dundurn, 2017)
Embattled Nation explores Canada's tense wartime election of 1917. Amidst the drama of the First World War, Canada's most divisive election ever raised pivotal questions about Canada's place in the war and the world. This book examines the issues, people, and events behind one of the most important elections in Canada's history.
Keywords: Borden, Robert Laird, -- Sir, -- 1854-1937.; Laurier, Wilfrid, -- Sir, -- 1841-1919.; Canada. -- Parliament -- Elections, 1917.; Borden, Robert Laird, -- Sir, -- 1854-1937; Laurier, Wilfrid, -- Sir, -- 1841-1919; Canada. -- Parliament; Canada -- Politics and government -- 1911-1921.; HISTORY -- Canada -- Post-Confederation (1867- ); 1917